(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Public Food Procurement emerges as a strategic tool for sustainable governance, capable of guiding an equitable and systemic food transition. This analysis takes a multilevel approach to the topic, focusing on minimum environmental criteria, spaces for innovation beyond mandatory regulations, and challenges related to food upcycling, novel foods, and the food sharing economy. It also highlights the importance of sharing best practices among public administrations. Particular attention is given to the indirect effects of public action through nudging and moral suasion to highlight the transformative potential of public food procurement in promoting sustainable behaviors and a new food ethic